2015
DOI: 10.5194/bg-12-1733-2015
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and carbon isotope composition of modern planktic foraminifera and near-surface waters in the Fram Strait (Arctic Ocean) – a case study

Abstract: Abstract. The upper 500 m of the water column and the sediment surface along an E-W transect in the Fram Strait were sampled for recent planktic foraminifera. The δ 18 O and δ 13 C values of the tests are compared to the stable isotope composition of the water samples taken from the same depths, and related to the characteristics of the water column. The polar species Neogloboquadrina pachyderma clearly dominates the species assemblage in the Fram Strait in the early summer, while the subpolar Turborotalita qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 55 publications
1
9
1
Order By: Relevance
“…Figure 1) which has relatively high δ 13 C values (cf. Pados et al, 2015). We note that the change from relatively high (~30%) to low (<20%) fragmentation around 8 ka in our core is opposite to what is observed in the deep Fram Strait (cf.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Figure 1) which has relatively high δ 13 C values (cf. Pados et al, 2015). We note that the change from relatively high (~30%) to low (<20%) fragmentation around 8 ka in our core is opposite to what is observed in the deep Fram Strait (cf.…”
Section: Discussioncontrasting
confidence: 69%
“…The δ 13 C values of planktic N. pachyderma were low in the Early Holocene part of our record (Figure 4a). Today, δ 13 C values of dissolved inorganic carbon (DIC) in western Fram Strait waters are highest in the upper 100 m (Pados et al, 2015). Further, a recent synoptic study revealed sea-ice coverage and the depth of the chlorophyll maximum as the major factors determining the vertical habitat of this species (Greco et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The δ 13 C values of N. pachyderma and T. quinqueloba in the water column in June do not show anomalously negative values, indicating no incorporation of CH 4 -derived carbon in their tests. Both δ 13 C and δ 18 O values of N. pachyderma and T. quinqueloba are comparable to those reported in the Fram Strait (Pados et al, 2015) 10.1029/2019JG005387…”
Section: Journal Of Geophysical Research: Biogeosciencessupporting
confidence: 78%
“…0 m). Neogloboquadrina pachyderma and N. incompta, which in Fram Strait prefer mainly Atlantic Water, are interpreted as indicators of subsurface water conditions and productivity at depths of about 250-75 m (e.g., Bé & Tolderlund 1971;Johannessen et al 1994;Volkmann & Mensch 2001;Simstich et al 2003;Pados & Spielhagen 2014;Pados et al 2015;Sarnthein & Werner 2017). Furthermore, we associate the SST TF estimated for 10-m water depth and the SST Mg/Ca based on N. pachyderma with surface and subsurface water temperatures, respectively.…”
Section: Interpretation Of Environmental Conditions At Storfjorden Famentioning
confidence: 99%